Entrepreneurial competency training instructor's manual - Diaz, Paz H.; Ching, Remedios S. ([Quezon City] EDCEL, PACSB, SERDEF, and U.P. ISSI, 1993)
A manual which aims to guide the intructor in teaching entrepreneurial competency in the Philippines. Intended for the use of teachers and instructors of entrepreneurship.
Keywords: Entrepreneurship -- Study and teaching -- Philippines -- Handbooks, manuals, etc; Small business -- Management -- Study and teaching -- Philippines -- Handbooks, manuals, etc; Competency based education -- Philippines -- Handbooks, manuals, etc